Upaya Guru Bimbingan dan Konseling dalam Mencegah Perilaku Bullying di SMA Negeri Se Kota Padang - Yunika, Riri; Alizamar, Alizamar; Sukmawati, inda (Konselor, 2013)
Bullying is a behavior consciously done by someone to abuse and hurt others. Ideally, the guidance and counseling teachers (BK teachers)are demanded to give attentions in preventing bullying behavior. However, in fact, the BK teachers have not plan special programs yet to prevent the bullying behavior among students in school. This research aims to describe the understanding of BK teachers about the concept of bullying behavior. Then, it aims to describe the treatment of the BK given by the teachers to the students. Finally, it aims to describe the cooperation among the BK teachers within the school. This research is kind of descriptive research. The population of this research is all of the BK teachers of SMA Negeri (State school for secondary education) in Padang. Sample is taken by using area sampling and simple random sampling techniques. Generally, the result implicates that the BK teachers have done preventing efforts toward bullying behavior among students in the school. Thus, the teachers should increase the understanding in reference to bullying behavior among students to prevent the behavior in school.